Review of firewall optimization techniques - Shakirah, Saidin; Mohamad Fadli, Zolkipli (Universiti Malaysia Pahang, 2018)
Firewall is a vital component in network security. Changes in requirements due to the growth of the Internet and increasing types of attack lead to the larger size of firewall policies and consequently affect the firewall performance. Hence, the network security policy will also be jeopardized. Minimizing firewall rules by removing anomalies in the policy proven to be one of the solutions. Firewall performance can also be optimized using data mining technique and optimization based on traffic awareness. This paper review firewall optimization techniques such as data mining, anomaly detection, and traffic awareness, that have been done throughout time. Suggestion to combine the removing anomalies technique and data mining technique to enhance firewall performance further is also mention in this paper. As a result, this paper will be useful for researchers who are interested in learning more about firewall optimization techniques.